A Case Report: Variation of the Cephalic and External Jugular Veins - Mohammad Reza Darabi; Alireza Shams; Parvindokht Bayat; Mohammad Bayat; Saeed Babaee; Bita Ghahremani (Negah Institute for Scientific Communication, 2015)
The knowledge of variations in the superficial veins is of clinical importance for the anatomist, radiologists, clinical practitioners and surgeons in order to plan about the operative procedures. Usually cephalic vein drains into the axillary vein. In this case report study the left cephalic vein communicates with the left external jugular vein and made a common trunk at the superior surface of the clavicle, and then opened into the subclavian vein posterosuperior to the clavicle. The aim of this report was to discuss about the presence of an abnormal communication between external jugular and cephalic vein.